Short course of glucocorticoids in patients with protracted and chronic gout arthritis. Part I: predictors of therapy efficacy - A A Fedorova; V G Barskova; I A Yakunina; V A Nasonova (Научно-практическая ревматология)
Objective. To reveal short course of glucocorticoid (GC) therapy efficacy predictors in pts with gout arthritis. Material and methods. 59 pts with tophaceous gout (crystal-verified diagnosis) and arthritis of three and more joints lasting more than a months in spite of treatment with sufficient doses of nonsteroidal anti-inflammatory drugs were included. Median age of pts was 56 [48;63], median disease duration - 15,2 years [7,4;20], median swollen joint count at the examination — 8 [5; 11]. The patients were randomized into 2 groups. Methylprednisolone was administered in one of them, betamethasone — in the other. Results, four variants of treatment response were described: full resolution of arthritis — 24 (41%), recurrent exacerbation — 28 (48%), insufficient arthritis resolution — 2 (3%) and clinically insignificant (unresponders) — 5 (8%) pts. Pts in group with arthritis recurrence at the entry were significantly younger than pts with resolved arthritis (52 [47;60] and 59 [52;68] respectively, U-test p=0,02), had more inflamed joints (9 [7,5; 11 ] and 5 [4;9[ respectively, U-test p=0,02), longer duration of last exacerbation (52 [8;52[ and 13 [7,5;52J respectively, U-test p>0,05), higher values of pain, joint index and swelling index (U-test p<0,04). Pts with insufficient arthritis resolution and unresponders had most severe gout course. Conclusion. The study allowed to reveal features which determine efficacy of short course of GC therapy in pts with protracted and chronic gout arthritis: inflamed joint count, duration of the last exacerbation and chronic renal insufficiency. Proposed an algorithm allowing to predict efficacy of GC short course in each pt.